Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Organizational Citizenship Behavior dengan Kepuasan Kerja sebagai Variabel Intervening pada PT Pelindo Multi Terminal Cilacap - Hari Sucahyowati; Dedeh Suryani (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2022)
The purpose of this study was to determine the effect of work environment and work motivation on Organizational Citizenship Behavior with job satisfaction as an intervening variable, with all employees of PT Pelindo Multi Terminal Cilacap as respondents. A quantitative approach was chosen to analyze the effect of each variable and use data sourced directly from all employees of PT Pelindo Multi Terminal Cilacap, which is presented in the Linkert scale. The application used is Partial Least Square (PLS) with SmartPLS version 3.2.9 program to present descriptive statistical data. SmartPLS was chosen as a test tool, because the sample used is not too large, and the hypothesis is made in the form of predictions. The results of this study indicate that the work environment has a significant influence on the variable job satisfaction, work motivation has an influence on job satisfaction, work motivation has an influence on Organizational Citizenship Behavior, work motivation has an influence on Organizational Citizenship Behavior, and the work environment has no influence on Organizational Citizenship Behavior. Job satisfaction as an intervening variable from the work environment has no effect on Organizational Citizenship Behavior. Job satisfaction as an intervening variable of motivation has a significant influence on Organizational Citizenship Behavior.